Primerjalna književnost v 20. stoletju in Anton Ocvirk - Dolinar, Darko; Juvan, Marko (Studia litteraria, 2008)
In the last few decades, comparative literature has spread even to those parts of the world that it had not reached before. However, at the same time it has faced a crisis in its traditional centers across Europe and North America, which has shaken its conceptual premises, theoretical foundations, and methodological structure, affected its inclusion in university and scholarly institutions, and jeopardized its social status. The discipline responded to this fundamental change through increased self-awareness and a true flourishing of relevant production directed towards fundamental reflections on its identity, the current situation, its genesis, and possible future paths.